1998
DOI: 10.1017/s0022377898006874
|View full text |Cite
|
Sign up to set email alerts
|

Generation of kinetic Alfvén waves by upper-hybrid pump waves

Abstract: The nonlinear mechanism for kinetic-Alfvén-wave (KAW) excitation by upper-hybrid waves (UHWs) is discussed. Taking into account perpendicular dispersion of KAWs, caused by effects of finite ion Larmor radius and electron inertia, we examine a new channel for UHW decay, in which a pump UHW decays into another UHW and an ultralow-frequency wave, KAW: UHW→KAW+UHW. A nonlinear dispersion relation is derived, and the growth rate of the parametric decay instability is calculated for a pump UHW propagatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Ïîñëåäíåå aeå ïðè îïðåäåëåííûõ äîïîëíèòåëüíûõ óñëîâèÿõ [9,14,15,18,19,23,48,50,51,54] ìîaeåò îáðàçîâàòü âñïëåñê èçëó÷åíèÿ â ìèêðîâîëíîâîì äèàïàçîíå, ÿâëÿþùèéñÿ ÷àùå âñåãî ïðåäâåñòíèêîì âñïûøêè â àêòèâíîé îáëàñòè (ÀÎ) [15,17,23,34,48,57]. Ñòîèò îñîáî îòìåòèòü, ÷òî ÊÀ è ÊÈÇ çàìå÷àòåëüíû íå òîëüêî òåì, ÷òî ÿâëÿþòñÿ íåèçìåííûìè ó÷àñòíèêàìè áîëüøèíñòâà òðåõâîëíîâûõ ïðîöåññîâ [51,[54][55][56], íî è ñàìè ïî ñåáå îáëàäàþò òàêèìè çàìå÷àòåëüíûìè ñâîéñòâàìè, êàê ðàñïàäíûé ñïåêòð [5,28,29] è ñîáñòâåííîå («ïðîäîëüíîå») ýëåêòðè÷åñêîå ïîëå [28,29], êîòîðîå ïîçâîëÿåò èì ýôôåêòèâíî ó÷àñòâîâàòü â ïðîöåññå óñêîðåíèÿ ÷àñòèö [45]. Ýòè âîëíû òàêaeå âåñüìà ýôôåêòèâíû â ïðîöåññå âîçíèêíîâåíèÿ â ïëàçìå àíîìàëüíîãî ñîïðîòèâëåíèÿ è íàãðåâàíèÿ ñðåäû [2-4, 12, 14, 28, 29].…”
Section: âñòóïëåíèåunclassified
“…Ïîñëåäíåå aeå ïðè îïðåäåëåííûõ äîïîëíèòåëüíûõ óñëîâèÿõ [9,14,15,18,19,23,48,50,51,54] ìîaeåò îáðàçîâàòü âñïëåñê èçëó÷åíèÿ â ìèêðîâîëíîâîì äèàïàçîíå, ÿâëÿþùèéñÿ ÷àùå âñåãî ïðåäâåñòíèêîì âñïûøêè â àêòèâíîé îáëàñòè (ÀÎ) [15,17,23,34,48,57]. Ñòîèò îñîáî îòìåòèòü, ÷òî ÊÀ è ÊÈÇ çàìå÷àòåëüíû íå òîëüêî òåì, ÷òî ÿâëÿþòñÿ íåèçìåííûìè ó÷àñòíèêàìè áîëüøèíñòâà òðåõâîëíîâûõ ïðîöåññîâ [51,[54][55][56], íî è ñàìè ïî ñåáå îáëàäàþò òàêèìè çàìå÷àòåëüíûìè ñâîéñòâàìè, êàê ðàñïàäíûé ñïåêòð [5,28,29] è ñîáñòâåííîå («ïðîäîëüíîå») ýëåêòðè÷åñêîå ïîëå [28,29], êîòîðîå ïîçâîëÿåò èì ýôôåêòèâíî ó÷àñòâîâàòü â ïðîöåññå óñêîðåíèÿ ÷àñòèö [45]. Ýòè âîëíû òàêaeå âåñüìà ýôôåêòèâíû â ïðîöåññå âîçíèêíîâåíèÿ â ïëàçìå àíîìàëüíîãî ñîïðîòèâëåíèÿ è íàãðåâàíèÿ ñðåäû [2-4, 12, 14, 28, 29].…”
Section: âñòóïëåíèåunclassified
“…Alexandrov, Bogdankevich, and Rukhadze, 1984). Yukhimuk et al (1998) have shown that the parametric decay of the upper-hybrid pump wave (UHW) into a kinetic Alfvén wave (KAW) and an EMW is possible in the solar atmosphere, i.e.,…”
Section: Wave Sources and Three-wave Interactionsmentioning
confidence: 99%
“…Since the pioneer work of Hasegawa and Chen 3 in 1975, the KAW has been applied extensively to various energization phenomena of plasma particles, such as tokamak plasma heating in the laboratory, 4,5 the flare plasma energization, 6,7 the plasma heating of solar coronal loops and plumes, 8,9 and the auroral electron acceleration in space plasmas. [10][11][12] Meanwhile, the generation of KAWs by various linear [13][14][15][16][17][18] and nonlinear [19][20][21][22][23] mechanisms has been diffusely studied.…”
Section: Introductionmentioning
confidence: 99%